Pelatihan dan Edukasi Penanaman dan Pemupukan Melon (Cucumis melo. L) dengan Pupuk Organik Cocopeat - Daud, Muhammad; Armia, Yasser; Hakim, Lukman; Aziz, Daska; Hasbaini, Hasbaini (Unity Academy, 2025)
This community service activity aims to improve community knowledge and skills in environmentally friendly melon farming using cocopeat fertilizer. Melon are horticultural commodities with high economic value that require proper planting and fertilization techniques to produce optimal production. The community service methodology is carried out through an educational, demonstrative, and direct practice approach in melon planting fields 50 participants. Training participants are given education, theory and direct practice regarding the preparation of planting media, fertilization methods, and direct fertilization of melon using cocopeat as a base fertilizer. Cocopeat has a high water and nutrient absorption capacity, so it can increase fertilization efficiency and soil fertility. The results of the community service activity show that overall around 75-90% of participants are able to understand and practice melon farming techniques using cocopeat properly and correctly. In addition, as many 85% of participants after in this training are able to understand the benefits of using cocopeat , the positive impacts, environmentally friendly, easy to obtain, cheap and effective and can increase the growth of melon. This community service activity is expected to be the first step in encouraging sustainable melon farming to increase the income of farmers. The conclusion of the community service activity regarding training and education on planting and fertilizing melon with cocopeat is very useful for participants and at the same time as a catalyst for change in terms of diversification of waste from coconut processing as the main raw material in making organic fertilizer which has utility value as a basic fertilizer for melon, so that participants can know and be motivated to realize an environmentally melon system.